Description of the larva of Epigomphus pechumani Belle (Odonata: Gomphidae) - Amaya-Vallejo, Vanessa; Bota-Sierra, Cornelio Andrés; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2026)
The larva of Epigomphus pechumani Belle, an endemic species of the Colombian Western Andes, is described, illustrated, and compared with other known Colombian congeners. The larva is characterized by the following combination of characters: third antennomere spindle-shaped, approximately 2.5× longer than its widest part; ligula with a ventral row of 9–12 short, truncate median teeth; lateral abdominal spines on S7–9 slightly divergent and upturned; mid-dorsal third of S8 light brown, S9 reddish brown, and S10 uniformly dark brown.